2020
DOI: 10.3389/fped.2020.586666
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Like Findings in a Fatal Case of Idiopathic Desquamative Interstitial Pneumonia Associated With IgA Glomerulonephritis in a 13-Month-Old Child

Abstract: In the COVID-19 era, patients with severe acute respiratory syndrome (SARS) are suspected to be associated with SARS-CoV-2 infection. The aim of this paper is to present a case with COVID-like pneumonia, with fatal evolution. The clinical aspects were correlated with the autopsy findings and discussed on the background of the most recent data from the medical literature. A 13-month-old girl was admitted to the emergency room with acute severe shortness of breath and pulmonary bilateral ground-glass opacities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…SARS‐CoV‐2 infection mainly affects the respiratory system with typical clinical symptoms of fever, dry cough, fatigue, dyspnea, hypoxemia, acute respiratory distress syndrome (ARDS), and multiple organ insufficiency 16 . Recent reports have suggested that SARS‐CoV‐2 infection can also affect the cardiovascular system, causing acute myocardial injury with rapid progression and poor prognosis in severe cases 2,8,9 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…SARS‐CoV‐2 infection mainly affects the respiratory system with typical clinical symptoms of fever, dry cough, fatigue, dyspnea, hypoxemia, acute respiratory distress syndrome (ARDS), and multiple organ insufficiency 16 . Recent reports have suggested that SARS‐CoV‐2 infection can also affect the cardiovascular system, causing acute myocardial injury with rapid progression and poor prognosis in severe cases 2,8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Li et al 29 have reported that cytokine storm may be an important mechanism of viral sepsis and MODS in patients with COVID‐19, including acute kidney injury. Furthermore, some autopsy findings have revealed that extensive endothelial cell damage in the heart, kidney, small intestine and liver in COVID‐19, 30 triggering excessive thrombin production, inhibiting fibrinolysis, and activating the complement pathway, causing a thrombotic inflammatory response, ultimately leading to microthrombus deposition and microvascular dysfunction, which may promote further evolution of acute tubular necrosis into cortical necrosis, resulting in irreversible renal failure 16,31 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations